Analysis Of Lifting Strength Of Padeye Subsea Structure Using Finite Element Method - Ali, Muhsin; Fadillah, Arif (International Journal of Marine Engineering Innovation and Research, 2025)
Indonesia's natural resources which are one of the sources of income for the Indonesian state, namely from the results of oil and gas management, subsea is one of the processes of exploring oil and natural gas which is increasing, with all the practicalities of technology and also the system it has and operational costs that are fairly cheap. Infield Umbilical Termination is one part of the subsea processing, which functions as a terminal for connecting electricity under the sea, therefore a construction is needed to protect the system from the Infield Umbilical Termination, known as the subsea structure so that it is protected from disturbances while in the sea. The construction process will never be separated from the activity called lifting. Padeye is an item to help lifting activities. the construction of the padeye plays a very important role when lifting is in progress because it is necessary to test the structural strength of the padeye. with the help of the finite element method, from the analysis results obtained the value of the structure experienced by the padeye at an angle of 45 degrees obtained the maximum stress value of 131.835 Mpa, Strain of 0.000433 mm, Displacement of 0.12 mm, Factor Of Safety 1149.413 and for an angle of 60 degrees obtained a stress value of 73.628 Mpa. Strain 0.000244, Displacement 0.0661 and Factor Of Safety 3.237. From the two stress values, the padeye structure can be declared safe, because it has not exceeded the yield strength value of the material of 345 MPa.